Hydrogen filling method and hydrogen embrittlement property evaluation method

JP7651254B2Active Publication Date: 2025-03-26NIPPON STEEL CORPORATION
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2019047572
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-04-04
Filing Date
2019-03-14
Publication Date
2025-03-26
Estimated Expiration
2039-03-14

AI Technical Summary

Benefits of technology

【0015】 本発明によれば、試料に水素を効率的に充填することが可能となる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007651254000001
    Figure 0007651254000001
Patent Text Reader

Abstract

To provide a method with which it is possible to efficiently fill a sample with hydrogen, and a method for evaluating the hydrogen embrittlement characteristic of the sample filled with hydrogen thereby.SOLUTION: Provided is a hydrogen filling method for a sample composed of a metal that includes, in a metallic phase, 95% or more by total volume of one or more selected from a bcc phase and a bct phase. The hydrogen filling method comprises the steps of: (a) immersing the sample and a counter electrode in an electrolytic solution; (b) adjusting the temperature Tc(°C) of the electrolytic solution so as to satisfy [Tc<20×ln(t)+55] in a relationship with a thickness t (mm) of the sample; and (c) causing a potential difference to occur between the sample and the counter electrode and electrochemically filling the sample with hydrogen.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hydrogen filling method and a hydrogen embrittlement property evaluation method. [Background technology]

[0002] In the development of high-strength steel, hydrogen embrittlement, in which strength and toughness are deteriorated by hydrogen, has become a major problem. However, the material structure changes related to hydrogen embrittlement are unclear, and there is a need to clarify the mechanism of hydrogen embrittlement. To do so, it is necessary to establish a method to efficiently fill hydrogen into steel.

[0003] As a method for filling hydrogen into steel, a method of electrochemically charging hydrogen is generally used (see, for example, Patent Documents 1 to 4). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2004-309197 A [Patent Document 2] JP 2013-124998 A [Patent Document 3] JP 2013-124999 A [Patent Document 4] JP 2016-57163 A Summary of the Invention [Problem to be solved by the invention]

[0005] In the above method, the sample and the counter electrode are immersed in an electrolyte, and a potential difference is generated between them to electrochemically charge the sample with hydrogen. However, the above literature does not fully consider the test conditions for hydrogen charging, and there is still room for improvement in order to more efficiently charge hydrogen into the sample.

[0006] The present invention aims to solve the above problems and provide a method for efficiently filling a sample with hydrogen, and a method for evaluating the hydrogen embrittlement properties of the sample filled with hydrogen thereby. [Means for solving the problem]

[0007] The present invention has been made to solve the above problems, and is summarized as the following hydrogen filling method and hydrogen embrittlement property evaluation method.

[0008] (1) A method for filling hydrogen into a sample made of a metal containing at least one type selected from a bcc phase and a bct phase in a total volume percentage of 95% or more in the metal phase, comprising: (a) immersing the sample and the counter electrode in an electrolyte; (b) adjusting the temperature Tc (°C) of the electrolyte in relation to the thickness t (mm) of the sample so as to satisfy the following formula (i): (c) generating a potential difference between the sample and the counter electrode to electrochemically charge the sample with hydrogen; How to fill hydrogen tanks. Tc<20×ln(t)+55 (i)

[0009] (2) In the step (b), the temperature of the electrolytic solution is adjusted so as to further satisfy the following formula (ii): The hydrogen filling method described in (1) above. Tc<10×ln(t)+30 (ii)

[0010] (3) In the step (b), the temperature of the electrolytic solution is adjusted so as to further satisfy the following formula (iii): A hydrogen filling method according to (1) or (2) above. Tc≦18 (iii)

[0011] (4) In the step (b), the temperature of the electrolyte is adjusted in relation to the molar mass concentration m (mol / kg) of the solute ions in the electrolyte so as to further satisfy the following formula (iv): A hydrogen filling method according to any one of (1) to (3) above. -1.86×m <Tc ···(iv)

[0012] (5) In the step (b), the distance between the sample and the counter electrode is adjusted to be greater than 0 mm and equal to or less than 100 mm. A hydrogen filling method according to any one of (1) to (4) above.

[0013] (6) A method for evaluating hydrogen embrittlement characteristics of a sample, comprising the steps of: The steps (a) to (c) described in any one of (1) to (5) above; (d) measuring the hydrogen concentration in the sample; Hydrogen embrittlement property evaluation method.

[0014] (7) A method for evaluating hydrogen embrittlement characteristics of a sample, comprising the steps of: The steps (a) to (c) described in any one of (1) to (5) above; (e) applying a stress to the sample; Hydrogen embrittlement property evaluation method. Effect of the Invention

[0015] According to the present invention, it is possible to efficiently fill a sample with hydrogen. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] A hydrogen filling method and a hydrogen embrittlement property evaluation method according to one embodiment of the present invention will be described in detail.

[0017] The hydrogen filling method according to one embodiment of the present invention includes (a) a soaking step, (b) a conditioning step, and (c) a hydrogen filling step. Each step will be described in detail below.

[0018] (a) Soaking process In the immersion step, the sample and the counter electrode are immersed in the electrolyte. In the present invention, the sample is made of a metal containing at least one selected from the bcc phase and the bct phase in the metal phase, with the total volume percentage being 95% or more. That is, the volume percentage of the fcc phase contained in the metal phase is 5% or less. The bcc phase includes ferrite, low carbon martensite, etc., and the bct phase includes high carbon martensite. The fcc phase includes austenite. There is no particular limitation on the shape of the sample. For example, it may be plate-shaped or cylindrical.

[0019] There is no particular restriction on the size of the sample, but from the viewpoint of stabilizing the accuracy of hydrogen concentration measurement, it is preferable that the sample weighs 0.5 g or more, and more preferably 1 g or more. If dirt or an oxide film is attached to the surface of the sample, the filling of hydrogen may be hindered. Therefore, it is desirable to clean the surface of the sample and remove dirt and oxide films.

[0020] The material of the counter electrode is not particularly limited, and for example, platinum can be used. The shape of the counter electrode is not particularly limited, and for example, a linear (rod) or plate-like electrode can be used. In order to efficiently fill the entire sample with hydrogen, it is preferable that the surface area of ​​the counter electrode relative to the surface area of ​​the sample satisfies the following formula (a). S2 / S1≧0.1 (a) In the formula (a), the meanings of the symbols are as follows: S1: Surface area of ​​the sample (mm 2 ) S2: Surface area of ​​the counter electrode (mm 2 )

[0021] Furthermore, there is no particular restriction on the components of the electrolyte, and it may be acidic, neutral, or alkaline. An aqueous NaCl solution is preferred as it is easy to prepare and easy to conduct electricity. In this case, the concentration of NaCl does not matter as long as the electrical conductivity is obtained, but it is preferable to set the concentration to, for example, 0.5 mass% or more.

[0022] In addition, if it is desired to fill a larger amount of hydrogen, an acid such as HCl or H2SO4 may be used, or a catalyst poison such as ammonium thiocyanate (NH4SCN) or thiourea may be added to the aqueous solution. On the other hand, from the viewpoint of suppressing corrosion of the sample, an alkaline aqueous solution such as NaOH may be used.

[0023] (b) Adjustment process In the adjustment step, the temperature of the electrolyte is adjusted. As described above, in the present invention, the sample is made of a metal mainly composed of a bcc phase and / or a bct phase. Most of the hydrogen filled in the bcc phase and / or the bct phase is trapped in defects such as dislocations, and the amount of trapped hydrogen increases at lower temperatures.

[0024] On the other hand, after the hydrogen filling process is completed, hydrogen diffusion from the sample surface occurs until the hydrogen amount measurement for hydrogen embrittlement evaluation is performed. However, hydrogen diffusion from the sample can be reduced by lowering the temperature of the sample. The lower the temperature of the electrolyte, the lower the temperature of the sample.

[0025] Here, the thinner the sample, the greater the decrease in the average hydrogen concentration in the sample due to hydrogen diffusion. Therefore, the thinner the sample, the greater the need to increase the amount of hydrogen filled and reduce hydrogen diffusion for efficient hydrogen filling. As a result of the above, the inventors have conducted research and found that hydrogen can be filled efficiently by adjusting the temperature of the electrolyte to a low level according to the thickness of the sample.

[0026] Specifically, when the temperature of the electrolyte is Tc (° C.) and the thickness of the sample is t (mm), the temperature of the electrolyte is adjusted so as to satisfy the following formula (i). Tc<20×ln(t)+55 (i)

[0027] Moreover, the temperature of the electrolytic solution is preferably adjusted so as to further satisfy the following formula (ii), and more preferably so as to satisfy the following formula (iii): Tc<10×ln(t)+30 (ii) Tc≦18 (iii)

[0028] The temperature of the electrolyte may be equal to or lower than 0° C. However, in order to set the temperature of the electrolyte to equal to or higher than the freezing point, it is preferable to adjust the temperature Tc (° C.) of the electrolyte so as to satisfy the following formula (iv) in relation to the molar concentration m (mol / kg) of the solute ions in the electrolyte. -1.86×m <Tc ···(iv)

[0029] In the present invention, the degree of ionization for salts formed from a strong acid and a strong base is set to 1, and for salts formed from a weak acid and a weak base, a weak acid and a strong base, or a strong acid and a weak base, the molar mass concentration of the ions is calculated from the degree of ionization.

[0030] The electrolyte is cooled and maintained at the set temperature using a immersion cooler or refrigerant circulator, etc. If the experiment is conducted in a location where the room temperature fluctuates above and below the set temperature, care should be taken to maintain the temperature by assembling the equipment so that the heater and cooler can be operated simultaneously.

[0031] In the present invention, the shortest distance from any point inside the sample to the sample surface is defined as L, and the maximum value of L is L max When this is done, 2L max is defined as the thickness of the sample. That is, if the sample is plate-shaped, the thickness is the plate thickness, and if the sample is cylindrical, the diameter is the thickness.

[0032] Furthermore, the total volume fraction of the bcc and bct phases is determined by the following method when the sample is steel. First, the sample is polished with 1200-grade Emily paper, and then immersed in a mixed solution of hydrofluoric acid and perchloric acid at room temperature to remove one-quarter of the thickness by chemical polishing. Next, X-ray diffraction measurements (Cu anticathode, tube voltage 30 kV, tube current 100 mA) are performed on the polished sample surface by a method based on Takeo Yazawa et al. (Iron and Steel, Vol. 83 (1997) No. 1, pp. 60-65), and the peak intensities of (111), (200), and (220) for the fcc phase, and (110), (200), and (211) for the bcc or bct phase are obtained, and the volume fraction of the fcc phase is calculated by a method based on Takeo Yazawa et al. The total volume fraction of the bcc and bct phases is then calculated by subtracting the obtained value from 100%.

[0033] If the sample is a metal other than steel, polish it and measure the X-ray diffraction in the same manner as above, and calculate the total volume fraction of the bcc and bct phases by subtracting the volume fractions of the fcc and hcp phases from 100%.

[0034] In the adjustment step, the distance between the sample and the counter electrode may be further adjusted. Until now, the distance between the sample and the counter electrode has not been considered as a factor that significantly affects the experimental results, and no special consideration has been given to it. In addition, it has generally been thought that a certain distance should be secured from the viewpoint of uniformity of the generated electric field.

[0035] However, the inventors investigated the relationship between the distance between the sample and the counter electrode and the amount of hydrogen filled, and found that, contrary to conventional thinking, the amount of hydrogen filled tends to increase as the distance becomes closer without causing contact.

[0036] Therefore, in the present invention, in the adjustment step, it is preferable to adjust the distance between the sample and the counter electrode to more than 0 mm and 100 mm or less. The shorter the distance, the more preferable, and it is preferably 50 mm or less, more preferably 10 mm or less, and even more preferably 5 mm or less. In addition, since it is necessary to avoid contact between the sample and the counter electrode, the distance is preferably 1 mm or more.

[0037] In the present invention, the distance between the sample and the counter electrode refers to the shortest distance between any point on the surface of the sample and any point on the surface of the counter electrode.

[0038] (c) Hydrogen filling process In the hydrogen filling process, a potential difference is generated between the sample and the counter electrode, and hydrogen is electrochemically filled into the sample. Specifically, the sample and the counter electrode are connected to an external power source via an electric wire or the like, a potential difference is generated between the sample and the counter electrode, and the sample is made negative in potential with respect to the counter electrode, whereby hydrogen is filled into the sample. In this case, for example, by using a potentiostat / galvanostat as the external power source, hydrogen can be filled by current control (constant current).

[0039] (d) Hydrogen concentration measurement process A hydrogen embrittlement property evaluation method according to one embodiment of the present invention includes, in addition to the above-mentioned steps (a) to (c), a step of measuring the hydrogen concentration contained in a sample. The hydrogen concentration may be measured after filling the sample with hydrogen by the above-mentioned method, or may be measured both before and after filling the sample with hydrogen. By measuring the hydrogen concentration in the sample, which is one of the important parameters for evaluating hydrogen embrittlement property, it is possible to evaluate the hydrogen embrittlement property of the sample.

[0040] There are no particular limitations on the method for measuring the hydrogen concentration in a sample. For example, the hydrogen concentration can be determined by using a gas chromatograph-type thermal desorption hydrogen analyzer (TDA) to heat the sample to 400°C at a heating rate of 100°C / h and then measuring the amount of released hydrogen.

[0041] (e) Stress application process A hydrogen embrittlement property evaluation method according to another embodiment of the present invention includes, in addition to the above-mentioned steps (a) to (c), a step of applying stress to a sample. The application of stress to the sample may be performed after the sample is filled with hydrogen by the above-mentioned method, or may be performed while the sample is being filled with hydrogen. There is no particular limitation on the type of stress applied to the sample, and it may be any of tensile stress, compressive stress, bending stress, and torsional stress. Then, for example, by measuring the stress at the time when fracture occurs, it is possible to directly evaluate the hydrogen embrittlement property of the sample.

[0042] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. EXAMPLES

[0043] A sample was made of JIS SCM435 steel, which is a low alloy steel and has a volume fraction of the bcc phase of 95% or more, and was filled with hydrogen. The dimensions and shape of the sample were a thin plate with a length of 20 mm, a width of 10 mm, and a thickness of 0.2 to 1.0 mm. A thin plate of platinum with a length of 30 mm, a width of 10 mm, and a thickness of 0.2 mm was used as the counter electrode. As the electrolyte, a 3% NaCl aqueous solution was used in Test Nos. 1 to 9, and a 5% NaCl aqueous solution was used in Test Nos. 10 to 12, and the temperature was adjusted to the temperature shown in Table 1.

[0044] The above sample and counter electrode were then immersed in the electrolyte, and the sample and counter electrode were arranged so that they were parallel to each other and separated by a distance of 30 mm. An external power source was used to generate a potential difference between the sample and the counter electrode, giving the sample a negative potential relative to the counter electrode. A potentio / galvanostat was used as the external power source, and the current density was set to 1.0 mA / cm. 2 The charging time was fixed at 24 hours.

[0045] [Table 1]

[0046] After that, the hydrogen concentration in each sample was measured. Specifically, the sample was heated to 400°C at a heating rate of 100°C / h using a TDA, and the amount of hydrogen released was measured to determine the hydrogen concentration in the sample. The results are shown in Table 1.

[0047] Referring to Table 1, in Test Nos. 3, 7, and 9, in which the temperature of the electrolyte did not satisfy formula (i), the hydrogen concentration was low, at 0.16 ppm, 0.11 ppm, and 0.15 ppm, respectively. In contrast, in Test Nos. 1, 2, 4-6, 8, and 10-12, which are examples of the present invention that satisfy formula (i), the hydrogen concentration was 0.20 ppm or more, which was a good result. In particular, in Test Nos. 1, 5, 8, and 10-12, in which the temperature of the electrolyte was 18°C ​​or less, the hydrogen concentration was 0.30 ppm or more, which was a remarkably good result. [Industrial Applicability]

[0048] According to the present invention, it is possible to efficiently fill a sample with hydrogen. Also, by employing the hydrogen filling method according to the present invention, it is possible to efficiently evaluate hydrogen embrittlement characteristics, which can contribute to elucidating the mechanism of hydrogen embrittlement.

Claims

1. A method for filling hydrogen into a sample made of steel containing at least one phase selected from a bcc phase and a bct phase in a metal phase at a total volume percentage of at least 95%, comprising the steps of: (a) immersing the sample and the counter electrode in an electrolyte; (b) adjusting the temperature Tc (°C) of the electrolytic solution in relation to the thickness t (mm) of the sample so as to satisfy the following formula (i) and further satisfy the following formula (iii): (c) generating a potential difference between the sample and the counter electrode to electrochemically charge the sample with hydrogen; How to fill hydrogen tanks. Tc<20×ln(t)+55...(i) Tc≦18...(iii)

2. In the step (b), the temperature of the electrolytic solution is further adjusted so as to satisfy the following formula (ii): The hydrogen filling method according to claim 1. Tc<10×ln(t)+30...(ii)

3. In the step (b), the temperature of the electrolytic solution is adjusted in relation to the molar mass concentration m (mol / kg) of the solute ions in the electrolytic solution so as to further satisfy the following formula (iv): The hydrogen filling method according to claim 1 or 2. -1.86×m<Tc...(iv)

4. In the step (b), the distance between the sample and the counter electrode is adjusted to be greater than 0 mm and equal to or less than 100 mm. A hydrogen filling method according to any one of claims 1 to 3.

5. 1. A method for evaluating hydrogen embrittlement characteristics of a sample, comprising the steps of: Steps (a) to (c) according to any one of claims 1 to 4; (d) measuring the hydrogen concentration contained in the sample; Hydrogen embrittlement property evaluation method.

6. 1. A method for evaluating hydrogen embrittlement characteristics of a sample, comprising the steps of: Steps (a) to (c) according to any one of claims 1 to 4; (e) applying a stress to the sample. Hydrogen embrittlement property evaluation method.

Citation Information

Patent Citations

  • Martensitic stainless steel for disk brake

    JP2001003142A

  • Method for evaluating resistance to delayed fracture

    JP2004309197A

  • Hydrogen embrittlement resistance characteristic evaluation method for thin steel sheet

    JP2013124998A

  • Hydrogen embrittlement resistance characteristic evaluation method for thin steel sheet

    JP2013124999A

  • Evaluation method of hydrogen embrittlement characteristic of steel material

    JP2016057163A